Management of non-malignant hyperinsulinemic hypoglycaemia in resource limited setting: a case report - Susanti, Vina Yanti; Vita Yanti Anggraeni; Leo, Benedreky (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
A 37 y.o. Asian male presented with frequent hypoglycaemia in both fasting and post-prandial state. He had elevated blood insulin levels during the hypoglycaemic episodes with normal pancreatic morphology and no extra-pancreatic tumor. Through systematic symptom assessment and the use of simple laboratory examination, non-insulinoma pancreatogenous hypoglycaemia syndrome presented as the most likely diagnosis. Conclusive aetiological diagnosis could not be reached due to the limited availability of diagnostic modalities. Nevertheless, modest symptom control and frequency reduction of hypoglycaemia were achieved with empirical dietary modification and α-glucosidase inhibitor treatment.